Effect of intrapartum oropharyngeal (IP-OP) suction on meconium aspiration syndrome (MAS) in developing country: A RCT. (December 2015) - Nangia, Sushma; Pal, Mansi M.; Saili, Arvind; Gupta, Usha
Abstract: Objective: Evidence about IP-OP suction and selective tracheal intubation in meconium stained neonates is from developed countries. Little information is available about their role in developing countries with high incidence of meconium staining and MAS. This randomized trial was planned to evaluate the effectiveness of IP-OP suction in meconium stained term neonates on prevention of MAS and reduction of its severity. Patients and methods: Out of 540 meconium stained full term, cephalic presentation, singleton neonates without major congenital malformations born from June'08 to January'09, 31 were excluded and 509 randomized. In the intervention group IP-OP suction was done at the time of delivery of head using a 10 Fr suction catheter with a negative pressure of 100 mmHg. No IP-OP suction was performed in control group. All neonates with MSAF were assessed as vigorous or non-vigorous after birth and provided care as per NRP guidelines 2005. Results: Two hundred and fifty three neonates were randomized to IP-OP suction and 256 to no IP-OP suction. Eighty-two neonates (16%) developed MAS, the primary outcome parameter, with 40 infants in the intervention group (15.8%) and 42 (16.4%) in the non-intervention group (RR 0.86, 95% CI 0.60–1.54). Incidence of severe MAS was comparable (3.55% vs. 2.34%) ( P value = 0.40). Other variables like requirement of oxygen >48 h (9.8% vs. 10.5%) and mortality (2.7% vs. 1.7%) were also comparable. Conclusions: IP-OP suctioning did not reduce the incidence or severity of MAS even in a setting of high incidence of MAS in a developing country. The mortality in two groups was comparable.